One pot hydrothermal synthesis of graphene like MoS2 nanosheets for application in high performance lithium ion batteries. Issue 71 (2nd August 2015) - Perumal Veeramalai, Chandrasekar; Li, Fushan; Xu, Hongyuan; Kim, Tae Whan; Guo, Tailiang
<x xml:space="preserve">Abstract</x> The excellent performance of hydrothermally synthesized MoS2 few layer nanosheets as a Li-ion battery anode material is demonstrated.